Rancang Bangun Aplikasi Laporan HVAC Menggunakan QR Code Berbasis Web - Ayu Prima Siska; Surya Aulia Rahman (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
PT Udara jadi Bersih Bekasi is a company engaged in testing Heating, Ventilation, and Air Conditioning (HVAC) systems. So far, the process of recording test results is still carried out manually using paper media. This process poses a number of obstacles, such as delays in recording, potential input errors, and limitations in accuracy and data storage. This condition also has an impact on delays in the submission of test results information to supervisors, who should need fast and accurate data for decision-making. To answer this problem, a web-based application is needed to design a web-based application that is able to digitize the entire workflow of recording and reporting HVAC test results. With a web-based system, data can be managed centrally, more structured, and easily accessible at any time. This application is also equipped with QR Code technology to speed up access to test results. Supervisors and technicians only need to scan the code for complete information, so they no longer rely on manual searches that are time-consuming and prone to serious errors in technical documentation. The design of this application uses the Waterfall method which consists of the stages of needs analysis, system design, implementation, testing, and maintenance. UML is used as a tool to describe business processes and system activity flows in detail, so that development can be carried out more systematically, efficiently, and in a targeted manner according to applicable software engineering standards. With the implementation of this application, PT Udara jadi Bersih Bekasi is expected to be able to improve operational efficiency, reduce recording errors, and speed up the information distribution process. In the end, this digitalization will support companies in providing services that are more professional, accurate, innovative, reliable, and according to the needs of the modern HVAC industry in the era of global digitalization.